1987
DOI: 10.1002/fut.3990070106
|View full text |Cite
|
Sign up to set email alerts
|

Option expirations and treasury bond futures prices

Abstract: ptions on financial futures are relatively new financial instruments, although 0 options on commodities have been in existence since the Nineteenth Century.The historical record of commodity options has been beset with problems, abuses and suspended operations.The prospects for commodity options remained bleak until 1981, when the Commodity Futures Trading Commission (CFTC) allowed options to be traded on organized exchanges for an initial three year period.' In view of the blemished record of commodity option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Klemkosky (1978) finds negative abnormal returns on the underlying stock in the week before the expiration of options listed on the Chicago Board Options Exchange that is partially reversed in the subsequent week. Pope and Yadav (1992) find similar, albeit smaller, effects in the U.K., and Bhattacharya (1987) finds no evidence of abnormal price behavior of bond futures contracts either before or after the date of option expiration. Pope and Yadav (1992) find similar, albeit smaller, effects in the U.K., and Bhattacharya (1987) finds no evidence of abnormal price behavior of bond futures contracts either before or after the date of option expiration.…”
Section: A Datamentioning
confidence: 93%
“…Klemkosky (1978) finds negative abnormal returns on the underlying stock in the week before the expiration of options listed on the Chicago Board Options Exchange that is partially reversed in the subsequent week. Pope and Yadav (1992) find similar, albeit smaller, effects in the U.K., and Bhattacharya (1987) finds no evidence of abnormal price behavior of bond futures contracts either before or after the date of option expiration. Pope and Yadav (1992) find similar, albeit smaller, effects in the U.K., and Bhattacharya (1987) finds no evidence of abnormal price behavior of bond futures contracts either before or after the date of option expiration.…”
Section: A Datamentioning
confidence: 93%
“…Previous studies, such as those of Bhattacharya (1987), Stoll and Whaley (1991), and Karolyi (1996), have found that expiration days are associated with abnormal trading volume, and the trading volume during last hour of expiration days can be as much as twice the normal trading volume. The results of testing the hypothesis that we will not observe a higher trading volume on the expiration day than on nonexpiration days are provided in Table VI.…”
Section: Volume Effectsmentioning
confidence: 96%
“…Relatively little research examines the impact of option expirations on other optionable assets. Bhattacharya (1987) does examine the expiration of options on Treasury-bond futures prices. Using daily price information for October 1982 through July 1985, Bhattacharya finds no evidence of abnormal price behavior in the Treasury-bond futures market either before or after the date of the option expiration.…”
Section: Option Expirations and Zjnderlying Asset Pricesmentioning
confidence: 99%